2019
DOI: 10.1088/1742-5468/ab4987
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic scale return coefficient with environmental feedback promotes cooperation in spatial public goods game

Abstract: In the traditional spatial public goods game (SPGG), the total contributions of each group are linearly amplified by the same enhancement factor, which does not coincide with the real situation. Although some literature has considered the non-linearity and heterogeneity of scale returns between groups, the dierences are completely generated by stochastic mechanisms. In addition, the coecient will not change once assigned in previous studies. In this paper, we consider an environmental feedback mechanism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Evolutionary game theory has supplied a universal framework to clarify how cooperation emerges, maintains and spreads among selfish individuals [3,4]. Within this framework, various famous game models including, but not limited to, the prisoner's dilemma game (PDG) [5,6], the snowdrift game (SDG) [7,8] and the public goods game (PGG) [9][10][11][12], have been commonly used to address various social dilemmas and make fruitful achievements [13][14][15][16], especially in the field of artificial intelligence [17,18]. In particular, the pioneering work by Nowak and May [19] and the fast development of complex networks [20,21] have further stimulated the investigation of evolutionary games using square lattice [14,22], small-world [23,24], and scale-free [25,26] networks, although a previous work [27] demonstrated that a square lattice might inhibit the evolution of cooperation in the SDG.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary game theory has supplied a universal framework to clarify how cooperation emerges, maintains and spreads among selfish individuals [3,4]. Within this framework, various famous game models including, but not limited to, the prisoner's dilemma game (PDG) [5,6], the snowdrift game (SDG) [7,8] and the public goods game (PGG) [9][10][11][12], have been commonly used to address various social dilemmas and make fruitful achievements [13][14][15][16], especially in the field of artificial intelligence [17,18]. In particular, the pioneering work by Nowak and May [19] and the fast development of complex networks [20,21] have further stimulated the investigation of evolutionary games using square lattice [14,22], small-world [23,24], and scale-free [25,26] networks, although a previous work [27] demonstrated that a square lattice might inhibit the evolution of cooperation in the SDG.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical physics provides a powerful tool in this direction [15,16]. Along this line of research, many micromechanisms for promoting cooperation have been proposed, such as introducing reward and punishment [17][18][19][20][21][22][23][24][25][26][27], social exclusion [28][29][30][31][32][33][34], considering individual or group heterogeneity [35][36][37][38][39], intelligent learning [40][41][42][43], and so on. Essentially, these mechanisms change the payoff structure of strategies or the rules of strategy updating.…”
Section: Introductionmentioning
confidence: 99%